G141(P) Monitoring respiratory function parameters in ventilated infants during inter-hospital emergency neonatal transport. (27th April 2015) - Bhat, P; Dhar, A; Chaudhary, R; O'Hare, S; Kent, S; Broster, S; Curley, A
Abstract : Introduction: Volume targeted ventilation (VTV) has been shown to decrease the incidence of hypocarbia, air leaks, bronchopulmonary dysplasia (BPD), intraventricular haemorrhage (IVH) and periventricular leukomlacia (PVL). As a result it has now become the predominant mode of ventilation in the NICU. Within the setting of a UK neonatal transport service, ventilation is more commonly non-triggered pressure limited and time cycled. End tidal Carbondioxide (ETCO) monitoring is used as a surrogate marker of ventilation and minute volume and has demonstrable effectiveness. There is a paucity of data however evaluating the use of additional respiratory function parameters, particularly tidal volume and tube leak during inter-hospital emergency neonatal transport. Aim: We aimed to assess current use of supplementary respiratory function monitoring within a UK neonatal transport setting. Methods: We carried out a telephonic survey of all UK neonatal transport teams to ascertain current practice with regards to monitoring of the following respiratory function parameters in ventilated infants during emergency neonatal transport: PIP, PEEP, MAP, minute volumes, flow, tidal volumes, ETCO and leaks around the ETT. Method of carbon dioxide monitoring was also recorded. Results: 21/22 (95%) of UK neonatal transport teams responded to the survey. Currently, during inter-hospital neonatal transport, 9/21(42%) teams monitor tidal volumes and 8/21(38%) teams monitor delivered airway pressures, flow, minute volumes and leaks around ETT. 18/21(85%) teams use ETCO monitoring. Of these, 14/18(77%) use side stream/micro stream and 4/18(23%) use mainstream ETCO monitoring. Conclusions: Our survey shows that currently, mechanical ventilation is mainly assessed using heart rate, respiratory rate, oxygen saturations, blood gas, chest rise, auscultation and ETCO monitoring. Hypocapnia is a well-known complication of mechanical ventilation and rates vary significantly between UK neonatal transport teams. Although the vast majority of teams use ETCO monitoring only 40% of services are using a measure of tidal volume. Continuous monitoring of ventilator parameters in an emergency situation and assessment of minute ventilation would allow clinicians to evaluate changes in pulmonary mechanics allowing short-term modifications, potential reductions in key outcome measures such as hypocarbia and possible reduction in medium to long-term adverse respiratory outcomes. Further studies of the potential benefits of enhanced monitoring are required in this high-risk area.